Determination of low wear rates in metal-on-metal hip joint replacements based on ultra trace element analysis in simulator studies - Kretzer, Jan Philippe; Krachler, Michael; Reinders, Jörn; Jakubowitz, Eike; Thomsen, Marc N.; Heisel, Jens Christian (Tribology letters, 2010)
Metal-on-metal joint bearings are being increasingly used for total hip arthroplasty. Previous results from simulator tests to determine wear of metal-on-metal bearings exhibited high fluctuations. Consequently, wear tests had to be performed for a long period of time to achieve stable values. The aim of this study was to establish a method for the precise measurement of wear of metal-on-metal bearings. Wear was determined by analyzing the concentrations of particles and selected elements in the test medium (serum) using high resolution-inductively coupled plasma-mass spectrometry (HR-ICP-MS). The procedure was first validated and compared to gravimetric measurements on two different implant designs and then applied in wear tests on four total hip resurfacing implants. The validation showed a significant reliability of the HR-ICP-MS method (p ≤ 0.02). The final wear test revealed that the HR-ICP-MS method can precisely detect very low wear rates and accurately characterize alterations in wear progression. The duration of simulation can be reduced due to the high detection power and low fluctuation in HR-ICP-MS wear determination analyses. This approach is suitable for test implants with extremely low wear rates.